Pendekatan DNA Barcoding untuk Identifikasi Cassidula angulifera (Petit, 1841) (Moluska: Gastropoda) - Dandi Saleky; Sendy L Merly (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
A large number of gastropod species have similarities in morphology (cryptic) makes misidentification probably happen/occurred. Accurate species identification is needed in studying bioecology of species. This research aims to identify the species of Cassidulla sp. Which was collected from Peyum Beach Merauke with DNA barcoding techniques using COI gene markers. The primers used in this study are forward primers (LCO1490) and reverse primers (HCO2198). The result of identification with DNA barcoding showed that the species analyzed was Cassidula angulifera with a 99.53% similarity level with a DNA sequence length of 650 bp. Phylogenetic reconstruction showing the entire sequence of Cassidula sp. which were analyzed separately based on the type and genetic distance with high bootstrap value. Phylogenetic reconstruction of Cassidula sp. form a monophyletic group, which means that the species come from the same ancestors. DNA barcoding is very good and accurate in identifying species.